EVENT MANAGEMENT ACTIVITY IN SMES – DO THEY NEED EDUCATED PERSONNEL? Does the supply and demand meet in case of event management education in Hungary? - Mondok, Anita (European Scientific Journal, ESJ, 2012)
Companies depending on their size and financial position are seeking for well-educated staff in event management. Some organizations have business in events management, but many are not operating in this sector, and for this latter group the motivation is train up or apply own staff to provide in-house capacity to set up and run events for themselves. Corporate management would require outside assistance is case of such occasions which are presented for a bigger degree and range of points that have to be handled or selections that should be considered are a lot larger sized. To examine the corporate behaviour in event management a survey on core competences in the field of events in small and medium sized enterprises and organizations was conducted in the scope of an EU Leonardo da Vinci Partnership project called COMPEVENT. This article introduce the key findings of research focusing on the place of organizing events in company organizational structure, the most commonly organized events and method of event organizing. Related to research results the Hungarian education market is assessed to find out whether the supply and demand meet in case of event management education.